Comparative assessment of sustainable development in South American countries on the basis of the Sustainable Society Index. Issue 1 (2nd January 2019) - Gonzalez-Cabezas, D.; Zaror, C.; Herrera, M. Á.
ABSTRACT: This study reports an overview of the economic, social and environmental performance of the main South American countries (SAC) as measured by the Sustainable Society Index. This is a well-known composite indicator, composed of 21 indicators, grouped in seven categories, covering environmental, social and economic wellbeing dimensions. Thirteen European countries recently incorporated into the European Union (NEUC) are considered as a reference. The study covers the period 2006–2016. The South American Region features significant natural resources and plays an important role in the global economy. However, there is concern about the long-term sustainability of social and economic development, given the high rate of economic growth based on the production of low added-value primary products. Sustainable development requires reasonable balance between economic, social and environmental performance, as well as a sustained and balanced increase in performance associated with those fundamental dimensions. Moreover, it is important to agree on minimum performance levels for all performance indicators, taking into account particular social, economic and environmental realities. SAC feature a clear imbalance in some categories affecting the economic, social and environmental wellbeing dimensions, showing either stagnation or significant decrease in recent years. It can be concluded that in the light of findings reported here, South American countries are far from being on the pathway towards sustainable development.